Enhanced phenol degradation at near neutral pH achieved by core-shell hierarchical 4A zeolite/Fe@Cu catalyst. Issue 5 (October 2020) - Huang, Lilan; Zhang, Leitao; Li, Deyuan; Xin, Qingping; Jiao, Rui; Hou, Xiaoyang; Zhang, Yuzhong; Li, Hong
Graphical abstract: Highlights: Using core-shell bimetallic catalyst enhances phenol degradation around neutral pH. The 4A zeolite/Fe@Cu had high utilization efficiency of H2 O2 . The Cu(II) nanosheets grown in-situ improved the stability of Fe(III). The open network structure of Cu(II) nanosheets avoided the embedding of Fe(III). Abstract: Delicate design of hierarchical and porous nanoarchitectures has become a highly effective strategy to develop novel bimetallic catalyst with improved stability and catalytic performance. Herein, a core-shell hierarchical 4A zeolite/Fe@Cu Fenton-like catalyst with 4A zeolite/Fe as core components and two-dimensional Cu hydroxide nanosheets assemblies as shell structure was fabricated through a simple and scalable approach and used for phenol degradation. The results indicated that 4A zeolite/Fe@Cu bimetallic catalyst had higher catalytic activity and utilization efficiency of H2 O2 than that of 4A zeolite/Fe and 4A zeolite@Cu monometallic catalysts at near neutral pH. In the presence of H2 O2, the 4A zeolite/Fe@Cu bimetallic catalyst could remove 95.3 % phenol after 4 h at pH 5, which was much higher than that of monometallic catalyst under the same condition. The enhanced activity of 4A zeolite/Fe@Cu was ascribed to the synergistic effect between the 4A zeolite/Fe (core) and two-dimensional Cu hydroxide nanosheets (shell). More importantly, the copper hydroxide nanosheets with open network structure on the surface of 4A zeolite/Fe@Cu improved the stability of the Fe(III) at acidic conditions, and avoided reduced catalytic efficiency of Fe(III) caused by embedding effect. This strategy provided guidance to the design of high-performance bimetallic Fenton-like catalysts.